HUMAN RESOURCES MANAGEMENT STRATEGY TO INCREASE EMPLOYEE PERFORMANCE - Ningsih (SEAN Institute, 2021)
In general, employee performance can be improved through increased compensation and work motivation. With the compensation provided by the company to employees, the enthusiasm, willingness, and thoroughness of employees at work will be maximized, focused, and disciplined. This study aims to determine and analyze the first strategy of human resource management in improving the performance of employees of PT Pelabuhan Indonesia 1 (Persero) Medan. Second, to find out the results of the SWOT analysis of the strategy for improving employee performance with the IFAS and EFAS matrices, it is possible to identify important factors from both the external and internal environment which are the strengths, weaknesses, opportunities and threats of improving performance. The research approach carried out in this study is descriptive qualitative, the author also uses SWOT analysis. SWOT analysis is the identification of various factors systematically to formulate corporate strategy. From the analysis results obtained a growth strategy or growth oriented strategy, this strategy indicates a strong company condition and is able to continue to grow by taking the opportunities and opportunities that exist to achieve maximum turnover. This strategy was chosen because the calculation results are in quadrant I where the total weighted score for strengths and weaknesses is 2.710504 while the total weighted score for opportunities is 2.653142. Positions in this quadrant are very profitable and can be applied to the fullest. SWOT analysis is the identification of various factors systematically to formulate corporate strategy. From the analysis results obtained a growth strategy or growth oriented strategy, this strategy indicates a strong company condition and is able to continue to grow by taking the opportunities and opportunities that exist to achieve maximum turnover.